JcMYB1, a Jatropha R2R3MYB Transcription Factor Gene, Modulates Lipid Biosynthesis in Transgenic Plants - Khan, K.; Kumar, V.; Niranjan, A.; Shanware, A.; Sane, V. A.
The lipid biosynthesis pathway in plants has been studied in detail; however, the factors that regulate the pathway at the transcription level are largely unknown. LEAFY COTYLEDON1 (LEC1), WRINKLED1 (WRI1)and FUSCA3 (FUS3)are considered master regulators to control seed oil content in Arabidopsis. Beside these master regulators, several other transcription factors that may regulate the pathway in plants are poorly studied. In the present work, we have shown the involvement of an uncharacterized Jatropha curcas R2R3MYB gene (JcMYB1)in seed oil biosynthesis. Seed oil analysis and expression profiling of fatty acid (FA)and triacylglycerol (TAG)biosynthetic genes in transgenic Arabidopsis and tobacco plants revealed that JcMYB1 enhances seed oil accumulation and alters FA composition by regulating the expression of endogenous pathway genes in transgenics. Using virus-induced gene silencing (VIGS)in Jatropha, we demonstrated that the suppression of JcMYB1 reduced lipid content with altered FA composition. Agro-infiltration and yeast one-hybrid assay results showed that JcMYB1 protein directly binds to the diacylglycerol acyltransferase1 (DGAT1)promoter, a rate-limiting enzyme of TAG biosynthesis, and activates its expression. These results suggested that JcMYB1 may augment the lipid content by regulating lipid biosynthetic genes. Additionally, manipulation of JcMYB1 in oil crop plants may be used for the potential improvement of oil production and quality.
Keywords: JATROPHA